The LOFAR Tied-Array all-sky survey: Timing of 21 pulsars including the first binary pulsar discovered with LOFAR. Issue 4 (10th February 2020) - Tan, C M; Bassa, C G; Cooper, S; Hessels, J W T; Kondratiev, V I; Michilli, D; Sanidas, S; Stappers, B W; van Leeuwen, J; Donner, J Y; Grießmeier, J-M; Kramer, M; et al.
ABSTRACT: We report on the multifrequency timing observations of 21 pulsars discovered in the LOFAR Tied-Array All-Sky Survey (LOTAAS). The timing data were taken at central frequencies of 149 MHz (LOFAR) as well as 334 and 1532 MHz (Lovell Telescope). The sample of pulsars includes 20 isolated pulsars and the first binary pulsar discovered by the survey, PSR J1658+3630. We modelled the timing properties of the pulsars, which showed that they have, on average, larger characteristic ages. We present the pulse profiles of the pulsars across the three observing bands, where PSR J1643+1338 showed profile evolution that appears not to be well-described by the radius-to-frequency-mapping model. Furthermore, we modelled the spectra of the pulsars across the same observing bands, using a simple power law, and found an average spectral index of −1.9 ± 0.5. Amongst the pulsars studied here, PSR J1657+3304 showed large flux density variations of a factor of 10 over 300 d, as well as mode changing and nulling on time-scales of a few minutes. We modelled the rotational and orbital properties of PSR J1658+3630, which has a spin period of 33 ms in a binary orbit of 3.0 d with a companion of minimum mass of 0.87 M⊙, likely a carbon–oxygen or oxygen–neon–magnesium type white dwarf. PSR J1658+3630 has a dispersion measure of 3.0 pc cm −3, making it possibly one of the closest binary pulsars known.